SRATEGI KONVERGENSI MEDIA CETAK HARIAN RIAU POS - Iis Patmanjawati; MUhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Developments in communication technologies today is very rapidly. The birth of digital media that uses Internet technology has affected the print media, where the number of circulation continues to decline from year to year. Print media that are still surviving are required to convergence by preparing digital-based media, one of wich is Riau Pos. As the purpose of this research is to find out the media convergence strategy carried out by Riau Pos.This study uses a qualitative method using media convergence teory, with the presentation of descriptive analisys by describing the state of the subject and object of research based on the existing facst. The data colection techniques were carried out trhough intervies with five informants using purposive sampling, documentation and observation. The data analysis techniques in this study used and interactive model by Miles and Huberman with the data analysis unit in the form of text/ sentence/ dialogue. To achieve the validity of the data in this study the authors used two data checking techniques, namely by extention of practicipation and triangulation techniques.The results showed that the convergence strategy of the daily Riau Pos industry has been ncarried out well. Planning and evaluation carried out by Riau Pos is decided be leadership of Riau Pos, besides that, the implementation of media convergence carried out by the Riau Pos daily is by unifying the newsroom. so that it can describe the Riaupos convergence strategy using the management function of media planning, organitation, actuating and controling. In addition, will describe how implementation of media convergence carried out by Riaupos daily is by providing a digital media platform in the from of e-paper, and providing social media such as Intragram, Facebook, Twitter and its Youtube channel, Raiupos.co for a young consumer audience. However, there are a number of things that need to be improved so the in the future Riaupos daily will still exist as a media company. Keyword : Convergence Strategy, Print Media Newspaper, Riau Pos Daily